Bank Capitalization As a Signal - Hardy, Daniel (Washington, D.C. : International Monetary Fund, 2012)
The level of a bank's capitalization can effectively transmit information about its riskiness and therefore support market discipline, but asymmetry information may induce exaggerated or distortionary behavior: banks may vie with one another to signal confidence in their prospects by keeping capitalization low, and banks' creditors often cannot distinguish among them - tendencies that can be seen across banks and across time. Prudential policy is warranted to help offset these tendencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet